Pitt–Hopkins syndrome (PTHS)– a case report from Pakistan - Nasir, Asghar; Afroze, Bushra; Ilyas, Saad; Ansar, Zeeshan; Hasan, Zahra (Journal of the Pakistan Medical Association, 2026)
Pitt–Hopkins syndrome (PTHS) is a rare genetic neurodevelopment disorder where affected individuals exhibit symptoms such as severe developmental delays and intellectual disability. To the best of our knowledge, this report presents the first known case from Pakistan where Chromosomal Microarray Analysis (CMA) was employed to diagnose PTHS. The CMA revealed a deletion in the Transcription Factor 4 (TCF4) gene, confirming the diagnosis. This case underscores the clinical features, diagnostic process, and the significance of CMA in diagnosing rare genetic disorders such as PTHS, particularly in resource-limited settings. Keywords: Pitt–Hopkins syndrome, TCF4 gene, Chromosomal Microarray Analysis, Pakistan case report.